Model Elaborasi Kognitif Siswa dalam Proses Abstraksi Prinsip dan Konsep Matematika Ruang Dimensi Dua di Kelas XI Teknik Las SMKN 1 Curup - Novianti Mandasari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
This study aims to describe the cognitive elaboration models of students in the process of abstraction of concepts and principles of two-dimensional mathematical space in Class XI of Las Teknik SMK 1 Curup. This research uses a qualitative approach. The main instrument is the researchers themselves guided by student ability test sheets and interview guide sheets. Data were analyzed through three stages, namely the stage of data reduction, data presentation and drawing conclusions. Research result; description of students' elaboration models in the process of abstraction of mathematical concepts in two-dimensional space: Recognizing models; Students are clearly familiar with the shapes of two-dimensional spaces, Students can understand the definition of two-dimensional shapes of two-dimensional space objects given, and based on information that students have obtained previously. Students can determine the objects that constitute the building of two-dimensional space. Students can discover the principles of building a two-dimensional space Model Building With; Students can discover the relationships of concepts and principles of two-dimensional geometric shapes by analyzing images of two-dimensional geometric objects. Model Contracting; Students know what concepts will be used, and to know these concepts students imagine and sketch a two-dimensional space object of the existing problems, in solving these problems associated with the incorporation of mathematical principles contained in the concept, and the student's knowledge according to students' ability to remember. Conclusion, through the concept of cognitive elaboration in the process of abstraction of principles and mathematical concepts of two-dimensional space students are able to use mathematical concepts and principles in solving problems so students are able to make conclusions from the results of the settlement and students are able to explain or present the results of their work. Keywords: Mathematical Concepts and Principles, Cognitive Elaboration Models, Abstraction Processes.